PENGARUH, KOMPETENSI, INDEPENDENSI DAN SKEPTISISME PROFESIONAL TERHADAP KUALITAS AUDIT ( Studi Empiris pada KAP di Kota Malang ) - Abdul Kadir Jailani; Nur Diana; Afifudin Afifudin (Universitas Islam Malang, 2019)
ABSTRACTThis study aims to determine the effect of competency, independence and professional skepticism on audit quality in KAP in Malang. This study uses a type of empirical research. The sample in this study were 59 respondent from 80 questionnaires distributed to auditor working at the Malang City Public Accountant Office. Data analysis in this study is using multiple linear regression models with SPSS analysis tool. The results of this study indicate that competency variables, independence variables and professional skepticism variables simultaneously have a significant effect on audit quality. While partially shows that the competency variable has a significant effect on audit quality, the independence variable has a significant effect on audit quality and the professional skepticism variable ha not significant effect on audit quality and the useful for the Public Accountant Office (KAP), especially in the city of Malang in making a decision, can also find out the factors that influence audit quality and audit service users can assess which KAP is consistent in maintaining audit quality. Keywords: Competency, Independence, Professional Skepticism, Audit Quality.